2007
DOI: 10.1152/ajplung.00365.2006
|View full text |Cite
|
Sign up to set email alerts
|

A role for CFTR in the elevation of glutathione levels in the lung by oral glutathione administration

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) protein is the only known apical glutathione (GSH) transporter in the lung. The purpose of these studies was to determine whether oral GSH or glutathione disulfide (GSSG) treatment could increase lung epithelial lining fluid (ELF) GSH levels and whether CFTR plays a role in this process. The pharmacokinetic profile of an oral bolus dose of GSH (300 mg/kg) was determined in mice. Plasma, ELF, bronchoalveolar lavage (BAL) cells, and lung tissue were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Because these previous studies focused on lung function parameters, clinical indicators concerning the growth failure typical of pancreatic insufficient CF patients were not examined in detail. In fact, there was some reason to believe that oral glutathione would be of little use in the treatment of CF patients [7]. Nevertheless, these results show that significant weight gain is also associated with use of this GSH regimen.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because these previous studies focused on lung function parameters, clinical indicators concerning the growth failure typical of pancreatic insufficient CF patients were not examined in detail. In fact, there was some reason to believe that oral glutathione would be of little use in the treatment of CF patients [7]. Nevertheless, these results show that significant weight gain is also associated with use of this GSH regimen.…”
Section: Discussionmentioning
confidence: 89%
“…Since the discovery that the CFTR channel was the major mechanism of GSH efflux into the extracellular milieu of the lung from lung epithelial cells and that this efflux was severely compromised in cystic fibrosis (CF) [1][2][3][4][5][6], resulting in glutathione system dysfunction and systemic deficiency of reduced glutathione (GSH) in CF, researchers have begun to explore what role glutathione system dysfunction plays in cystic fibrosis disease. Not only have in vitro studies proven useful in the development of new hypotheses in this regard [7][8][9][10][11][12][13][14][15][16][17], but several clinical trials of GSH or GSH precursors such as NAC have resulted in improvement in clinically-relevant markers in CF patients [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that NAC (2.5 mmol/kg) ip 1 h prior to acetaminophen (5 mmol/kg) treatment was effective in preventing increases in plasma alanine aminotransferase (ALT) activities (Gomez et al, 1994). Kariya et al (2007) found that 1 h after an oral dose of 300 mg/kg GSH, GSH levels in lung tissue increased twofold. A study by Vina et al (1989) showed that administration of GSH orally was sufficient to increase GSH levels in fasted rats, as well as in mice treated with the GSH-depleting agent diethyl maleate.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have shown that CFTR facilitates glutathione efflux into luminal fluids, either directly by serving as a glutathione channel (33,36) or indirectly by affecting the activity of other glutathione transporters (19), with the luminal glutathione serving an antioxidant function. Previous studies have demonstrated that glutathione efflux is reduced in cells lacking a functional CFTR (19,20), and reduced levels of GSH have been reported in extracellular bronchoalveolar lavage fluid from both CF patients (7,47) and mice (8,30,57).…”
Section: Surface the Effects Of Inhibitors Of Namentioning
confidence: 98%